The Correlation Among Knowledge, Nutritional Status and Income with Incidence of Infant Mortality Rate in Grobogan Regency - Istiqomah, Annisa Aulia; Yuniastuti, Ari; Rahayu, Sri Ratna (Public Health Perspective Journal, 2021)
In 2018 Infant Mortality Rate (IMR) in Grobogan increased into the third-highest death rate. It was 14.27 per 1,000 live births, and in 2019 Infant Mortality Rate in Grobogan was 14.61 per 1,000 live births, namely 284 deaths from 19,427 births. The purpose of this study was to determine the risk factors associated with IMR in Grobogan Regency from 2019 to 2020. The type of research used a case-control study with 60 cases and 60 controls as the sample. The instrument used a structured questionnaire sheet. Data analysis was performed by univariate and bivariate using the chi-square test. The results showed that the risk factors associated with the incidence of IMR include knowledge (P-Value = 0.000), maternal nutritional status during pregnancy (p-value = 0.000), and income (P-value 0.058). The conclusion of this study stated that there is a correlation between knowledge and nutritional status during pregnancy, but the income variable is not related to the incidence of IMR in Grobogan Regency.